Pueblo Indians and Spanish Colonial Authority in Eighteenth-Century New Mexico - Brown, Tracy L. (Book collections on Project MUSE., 2013)
This book investigates the tactics that Pueblo Indians used to negotiate Spanish colonization and the ways in which the negotiation of colonial power impacted Pueblo individuals and communities. -- Provided by publisher.